Evaluating IT Service Capability of Palu BPS Website Using COBIT 5 Framework - Ningsih, Alief Surya; Lapatta, Nouval Trezandy; Laila, Rahmah; Kasim, Anita Ahmad; Joefrie, Yuri Yudhaswana; Anshori, Yusuf (Universitas Raharja, 2026)
This research assesses the IT service capability of the official website of the Palu City Central Bureau of Statistics (BPS) by applying the COBIT 5 framework. The assessment is centered on four key processes from the Deliver, Service, and Support (DSS) as well as Monitor, Evaluate, and Assess (MEA) domains—namely DSS01 (Manage Operations), DSS02 (Manage Service Requests and Incidents), DSS06 (Manage Business Process Controls), and MEA01 (Monitor, Evaluate, and Assess Performance and Conformance). Data were collected through structured interviews, observation sessions with website administrators, and an analysis of supporting documents to determine the current capability levels and compare them with the desired target level of 3. The results show that DSS01 and MEA01 have reached capability level 2, indicating that the processes are defined but not consistently standardized. Meanwhile, DSS02 and DSS06 remain at level 1, indicating reactive operations with limited documentation. The average capability level of 1.5 suggests that there is room for significant improvement in terms of documentation, process formalization, and the use of enabling technologies. Based on these findings, this study recommends targeted improvements to enhance the overall performance and reliability of digital public services, as well as to support better IT governance and e-government practices.